BIODIVERSITAS GASTROPODA DI HUTAN MANGROVE SEGARA ANAKAN CILACAP - Dewi Kresnasari; Mei Gitarama, Arbi (Badan Perencanaan Pembangunan Penelitian dan Pengembangan Daerah Kabupaten Cilacap, 2024)
Segara Anakan is a lagoon surrounded by swamp forest with a mud substrate. Several biota live in it, one of which is Gastropods. This biota has slow movements and is relatively sedentary. The aim of research on gastropod biodiversity is to describe the diversity and dominance of their species. The research was conducted in July-September 2021. The research method used was a survey with a purposive random sampling technique at three stations taking into account differences in vegetation community structure. Station 1 (St 1) is in the eastern part of Segara Anakan with vegetation that dominates Aegiceras corniculatum; Station 2 (St 2) is in the middle of Segara Anakan with vegetation that dominates Nypa fruticans; Station 3 (St 3) is in the western part of Segara Anakan with vegetation dominating Sonneratia alba. Each station is determined by nine different sampling points once every month. The results showed that the Potamididae and Neritidae families were most commonly found at all stations during the study. The highest abundance is found in St 3, namely 1433 ind/m2, the lowest in St 1, namely 545 ind/m2. The diversity index in the medium category is at St 1 (1.05) and St 3 (1.59), while the low category is at St 2 (0.85). The dominance index in the medium category is at St 2 (0.55), and in the low category at St 1 (0.47) and St 3 (0.28). Factors that influence differences in abundance, diversity and dominance are adaptation, food and environmental conditions in which they live.